PERKEMBANGAN BISNIS FRANCHISE - Ayu Dwi Puspitasari; Ana Susi Mulyani (JISOS: JURNAL ILMU SOSIAL, 2022)
This article aims to explain how this franchise or franchise business runs and how the content in this business is how to be able to establish and also show shortcomings in this business. This article also explains the history of how this franchise business began and how it spread to the world of globalization and is associated with current technological developments. This article also discusses how this business is developing now, especially in Indonesia. This business has lucrative benefits for people who want to start a business but don't really want to put in more effort and don't want to take big risks. But this business also has drawbacks such as a lack of ownership in the business because management and the target market are not determined by us but the brand owners themselves plus this business is very dependent on trends or depending on something that is viral on social media in this way many consumers are stuck in trends market